Cocaine-associated increase of atrial natriuretic peptides: an early predictor of cardiac complications in cocaine users?. Issue 1 (8th July 2014) - Casartelli, Alessandro; Dacome, Lisa; Tessari, Michela; Pascali, Jennifer; Bortolotti, Federica; Trevisan, Maria Teresa; Bosco, Oliviero; Cristofori, Patrizia; Tagliaro, Franco
Abstract : Objective: Cocaine is known to produce life-threatening cardiovascular complications, and the investigation of the causes of death may be challenging in forensic medicine. The increasing knowledge of the cardiac function biomarkers and the increasing sensitivity of assays provide new tools in monitoring the cardiac life-threatening pathological conditions and in the sudden death investigation in chronic abusers. In this work, cardiac dysfunction was assessed in an animal model by measuring troponin I and natriuretic peptides as biomarkers, and considering other standard endpoints used in preclinical toxicology studies. Methods: Lister Hooded rats were treated with cocaine in chronic self-administration studies. Troponin I (cTnI) and atrial natriuretic peptide (ANP) were evaluated at different time points and heart weight and histopathology were assessed at the end of the treatment period. Furthermore, cocaine and its main metabolites were measured in the rat fur to assess rats' cocaine exposure. All the procedures and endpoints considered were designed to allow an easy and complete translation from the laboratory animals to human beings, and the same approach was also adopted with a group of 10 healthy cocaine abuse volunteers with no cardiac pathologies. Results: Cardiac troponin I values were unaffected, and ANP showed an increasing trend with time in all cocaine-treated animals considered. Similarly, in the healthy volunteers, no changes were observed in troponin serum levels, whereas the N-terminal brain natriuretic pro-peptide (NT proBNP) showed variations comparable with the changes observed in rats. Conclusions: In conclusion, natriuretic peptides could represent an early indicator of heart dysfunction liability in chronic cocaine abusers.